2016
DOI: 10.1097/mnm.0000000000000444
|View full text |Cite
|
Sign up to set email alerts
|

The combination of 13N-ammonia and 18F-FDG whole-body PET/CT on the same day for diagnosis of advanced prostate cancer

Abstract: PurposeThe aim of the study was to evaluate the efficacy of 13N-ammonia and 18F-fluorodeoxyglucose (18F-FDG) PET performed on the same day in the detection of advanced prostate cancer (PC) and its metastases.Patients and methodsTwenty-six patients with high-risk PC [Gleason score 8–10 or prostate-specific antigen (PSA)>20 ng/ml or clinical tumor extension≥T2c] were recruited into the study. 13N-Ammonia and 18F-FDG PET/CT were performed on the same day (18F-FDG followed ammonia, with an interval of a minimum of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Three studies reported on other imaging modalities such as 18 FDG-PET/CT, 11C-acetate-PET/CT, or 13N-ammonia-PET/ CT and reported promising results [124,143,144]. Two studies assessed the use of FDG-PET/CT for primary staging.…”
Section: Other Pet Tracersmentioning
confidence: 99%
See 2 more Smart Citations
“…Three studies reported on other imaging modalities such as 18 FDG-PET/CT, 11C-acetate-PET/CT, or 13N-ammonia-PET/ CT and reported promising results [124,143,144]. Two studies assessed the use of FDG-PET/CT for primary staging.…”
Section: Other Pet Tracersmentioning
confidence: 99%
“…Two studies assessed the use of FDG-PET/CT for primary staging. While FDG-PET/CT remained less useful for relatively welldifferentiated tumors, favorable sensitivity for FDG-PET/CT (90-100%) was observed in high-risk patients [124,144,145]. When compared with 13N-ammonia, both tracers had perfect sensitivity for the detection of bone metastases [144].…”
Section: Other Pet Tracersmentioning
confidence: 99%
See 1 more Smart Citation
“…Sometimes SSMs can break through the diaphragma sellae and grow into the pituitary fossa making it difficult to differentiate them from NFPMAs extending anteriorly and superiorly on usual morphological imagings [7,18] . PET/CT as one of the most important molecular imaging modalities has been confirmed to be satisfied in the accurate prediction of brain tumors and widely used in clinical practice with various tracers [19][20][21] .…”
Section: Discussionmentioning
confidence: 99%
“… 23 On the other hand, tumors with low metabolic rates, such as the mucinous adenocarcinomas, or weak glucose avidity, such as some prostate cancers, can be associated with equivocal or negative scans. 24 , 25 Also, it is impossible to discriminate between the glucose oxidative pathway and anaerobic consumption when using 18 F-FDG because it is not metabolized beyond phosphorylation. 11 C-glucose could be used as an alternative to follow the anaerobic and oxidative pathways, but PET imaging only detects the presence of radioactivity and not the type of carrier; therefore, it cannot differentiate between the native radiotracer and its metabolites.…”
Section: Pet Metabolic Biomarker and Cell Metabolismmentioning
confidence: 99%